Thinking Mindfully About Parenting and Parenting Education - McDermott, Dana (Child welfare, 2006)
This volume is dedicated to advances in the theory, research, and practice of parenting education and support, and it reflects CWLA's and the National Parenting Education Network's focus on improving the lives of children by supporting the parents and care providers who nurture and guide them. The work of CWLA is well known to readers but that of the National Parenting Education Network (NPEN) may not be. In this introduction, NPEN's vision, mission, and core principles are briefly described (see www.npen.org for further elaboration), and an overview of the articles included in this volume is provided.